Effects of Nigella sativa on VCAM-1 and ICAM-1: A systematic review of preclinical and clinical studies - Faghfoori, Zeinab; Javadivala, Zeinab; Malek Mahdavi, Aida (Journal of cardiovascular and thoracic research, 2025)
The objective of present review was to assess all studies about effect of Nigella sativa (N. sativa) on vascular cell and intercellular adhesion molecules-1 (VCAM-1 and ICAM-1) under different situations. Search was performed until May 2024 using Scopus, PubMed, Web of Science, and Google Scholar databases without any restriction and alert services were utilized following the primary search. The references cited in related papers were also evaluated. Nineteen studies including human (n=4), animal (n=11), and in vitro (n=4) were eligible. All in vitro and majority of animal researches were indicative of the favorable effects of N. sativa and thymoquinone in attenuating VCAM-1 and ICAM-1 levels; however, three animal studies did not show any significant effect. Results of clinical trials were conflicting. In two clinical trials, supplementation with N. sativa oil and N. sativa powder led to significant reduction in VCAM-1 levels in coronary artery disease (CAD) and Hashimoto’s thyroiditis patients, whereas no significant change occurred according to the other clinical trial involving subjects with the risk factor for cardiovascular disease (CVD). Furthermore, significant reduction in ICAM-1 levels occurred after N. sativa oil consumption in two clinical trials involving type 2 diabetic and CAD patients, whilst no significant change was noticed in subjects with the risk factor for CVD and Hashimoto’s thyroiditis patients. N. sativa seems beneficial in attenuating VCAM-1 and ICAM-1 levels under different situations; however, additional long-term controlled clinical trials are needed for making concise conclusions about the effect of N. sativa on endothelial dysfunction related biomarkers.